Structural and optical properties of pure ZnO and Al/Cu co-doped ZnO semiconductor thin films and electrical characterization of photodiodes - Demirbilek, Nihat; Yakuphanoğlu, Fahrettin; Kaya, Mehmet (Walter de Gruyter Gmbh, 2021)
Nano-structured semiconductor thin films and p-type Si photodiodes were fabricated with the sol-gel spin coating technique using pure ZnO and co-doped. ZnO:Al-x:Cu-y with x = 1 at.-%, y = 1, 2, 3, 5 at.-%. The structural and optical properties of thin films were examined using an XRD and a UV-spectrophotometer. The thin films have a hexagonal wurtzite crystal structure, and their optical band gap energies decrease with increasing Cu contribution. The electrical properties of photodiodes were assessed via I-V, C-V, (G/co)-V and phototransient current (14, C-t) measurements. The Phi(b(I-V)), experimental zero-bias barrier height, rectification ratio, ideality factor and I-on/I-off parameters of the diodes were calculated using thermoionic emission model. In addition, Phi(b(C-V)), barrier height, V-bi, built:-in voltage, V-d, diffusion potential, N-d, donor concentration and W-d, depletion layer width of p-SignO:Al-x:Cu-y (x = 1 at.-%, y = 1 at.-%.) photodiodes were obtained using a C-2-V graph plotted at 1 MHz frequency. The photodiodes exhibit rectifying and photosensitive behaviors, and their reverse bias current increases with increasing light intensity. These results indicate that produced diodes can be employed as photodiodes or photosensors in optoelectronic circuits and electronic devices.
Keywords: Sol-gel; photodiode; ZnO; nanostructure; optical properties; semiconductors